2006
DOI: 10.1111/j.1365-2036.2006.00026.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in biochemical parameters related to atherosclerosis after Helicobacter pylori eradication

Abstract: SUMMARY BackgroundRecent evidence suggests that Helicobacter pylori infection is involved in the pathogenesis of extra-gastrointestinal diseases such as coronary heart disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 46 publications
2
19
0
Order By: Relevance
“…In metabolic risk factors for atherosclerosis, HDL-cholesterol was decreased and TG was slightly increased, although BMI was lower 25) in AG subjects in our study. These results were consistent with previous reports 26,27) . It has been shown that HDL-cholesterol was significantly decreased in HP-positive elderly subjects 28,29) .…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…In metabolic risk factors for atherosclerosis, HDL-cholesterol was decreased and TG was slightly increased, although BMI was lower 25) in AG subjects in our study. These results were consistent with previous reports 26,27) . It has been shown that HDL-cholesterol was significantly decreased in HP-positive elderly subjects 28,29) .…”
Section: Discussionsupporting
confidence: 83%
“…It has been shown that HDL-cholesterol was significantly decreased in HP-positive elderly subjects 28,29) . HDL-cholesterol has been shown to increase after successful eradication of HP 26,27) . It has also been reported that HP affects other lipid profiles, such as total cholesterol 30) , LDL, and lipoprotein-a 28) ; however, total cholesterol and LDL-cholesterol were not different according to AG or HP status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An adversely altered lipid profile, including an increased LDL-c level and decreased HDL-c level, is one of the most important risk factors for atherosclerotic disease. Furthermore, a study performed in Japan showed a significant increase in the HDL-c level and significant decrease in the LDL-c level after successful H. pylori eradication; this effect was sustained over three years of follow-up 128) . Hence, it is conceivable that H. pylori infection functions as a predisposing factor for atherosclerotic processes by modifying the serum lipid profile.…”
Section: H Pylori Related-inflammation and Atherosclerosismentioning
confidence: 99%
“…Both triglycerides and total cholesterol levels decreased gradually (from 132 to 129 mg/dL and from to 170 to 168 mg/dL, respectively) with a significant trend towards an increase in HDL cholesteremia (from 48 to 52 mg/dL; p 0.0201) levels and non-significant decrease in LDL cholesteremia (from 140 to 137 mg/dL; p 0.4136) levels 7) . In a similar study performed in Japan, Ando et al reported a significant increase in HDL cholesteremia levels and a significant decrease in LDL cholesteremia levels after bacterial eradication 8) .…”
Section: Lipid Profile and Helicobacter Pylori Infectionmentioning
confidence: 84%